Chironomidae larvae as bioindicators of an acid mine drainage in Portugal - Bisthoven, L. Janssens de
The abandoned Sao Domingos mine in South Portugal discharges acid metal pollution in the drainage system. A dynamic pH- and metal-gradient (pH 3.3-6.8) modulated by rainfall at the confluence of a tributary with the acid mine drainage (AMD)-channel, and a small reservoir contaminated with arsenic were sampled for Chironomidae in three different seasons and compared with a control river, to test whether this insect family is sensitive to AMD-pollution and arsenic. The AMD sites contained 18-22 taxa, compared to 22 taxa in the reservoir and 25 taxa in the control site. The chironomid fauna in the AMD was characterised by a high proportion of Chironominae and predatory Tanypodinae, and a low proportion of Orthocladiinae, these subfamilies being useful and easy bioindicators for AMD. The presence of morphological deformities in Ablabesmyia monilis and Procladius sp. is a potential bioindication of AMD but due to low numbers of larvae, it was of limited use. Despite high arsenic levels in the water, the small reservoir contained many taxa forming a typical lentic community.